Potensi Buah Pare (Momordhica Charantia) Sebagai Agen Pengobatan Ulkus Peptikum - Ellyta Septyarani (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Peptic ulcer is a condition of damage to the mucosal tissue, submucosa to the muscular layer of the digestive tract and is in direct contact with stomach acid / pepsin. The cause of peptic ulcers is related to H pylori and Non-steroidal Anti-Inflammatory Drugs (NSAIDs). H pylori infection accounts for 90% of duodenal ulcer and 70% -90% of gastric ulcer. A systematic eview in 2018 found Spain to have the highest annual incidence of 141.8 / 100,000 people, while Britain had the lowest of 23.9 / 100,000 people and the prevalence of peptic ulcer in Indonesia is 6-15% especially at the age of 20-50 years with a peak age of 50-60 years. Herbal plants are traditional medicines that have been used all over the world because they are easy to get, cheap, and can provide their own lessons. Currently being used the use of Pare (Momordhica charantia) as a Peptic Ulcer Treatment Agent.Topical injury initiates erosion of initiation by disrupting the defense of the gastric epithelial mucosa. Studies in mitochondria and various cells show the accumulation of 'ion trapping' or ions trapped in gastric epithelial cells with mitochondrial oxidative phosphorylation and the inhibition of the work of the electron transport chain. This results in no formation of intracellular ATP, cellular Ca ++ toxicity and buildup of Reactive Oxygen Species (ROS) as free radicals.Momordica charantia is a family plant of Cucurbitaceae which has leaves, flowers and fruit. This plant shows considerable activity in reducing oxidative stress caused by reactive oxygen species that can treat peptic ulcers.